Offline Handwritten Signature Verification using Ne ural Network - Pallavi V. Hatkar; Prof.B.T.Salokhe; Ashish A.Malgave (International Journal of Innovations in Engineering Research and Technology, 2021)
The different biometric techniques have been discussed for identification. Such as face reading, fingerprintrecognition and retina scanning and these are known as vision based identification. There are non vision basedidentifications such as signature verification and the voice recognition. Signature verification plays a vital rolein the field of the financial, commercial and for the legalmatters. Signature by any person considered as theapproval for any work so the signature is the preferred authentication. In this paper signature verification isdone by means of image processing, geometric feature extractionand by using neural network technique.